Frailty in patients with acute coronary syndrome: comparison between tools for comprehensive geriatric assessment and the Tilburg Frailty Indicator - Uchmanowicz I (Dove Medical Press, 2015)
Izabella Uchmanowicz,1 Magdalena Lisiak,1 Radosław Wontor,2 Krystyna Łoboz-Grudzień1,21Department of Clinical Nursing, Wrocław Medical University, Wrocław, Poland; 2Department of Cardiology, T Marciniak Memorial Hospital, Wrocław, PolandPurpose: It is a known fact that age is a strong predictor of adverse events in acute coronary syndrome (ACS). In this context, the main risk factor in elderly patients, ie, frailty syndrome, gains special importance. The availability of tools to identify frail people is relevant for both research and clinical purposes. The purpose of this study was to investigate the correlation of a scale for assessing frailty – the Tilburg Frailty Indicator (TFI) and its domains (mental and physical) – with other research tools commonly used for comprehensive geriatric assessment in patients with ACS.Patients and methods: The study covered 135 people and was carried out in the cardiology ward at T Marciniak Lower Silesian Specialist Hospital in Wroclaw, Poland. The patients were admitted with ACS. ST segment elevation myocardial infarction and non-ST segment elevation myocardial infarction were defined by the presence of certain conditions in reference to the literature. The Polish adaptation of the TFI was used for the frailty syndrome assessment, which was compared to other single measures used in geriatric assessment: the Mini-Mental State Examination (MMSE), the Hospital Anxiety and Depression Scale (HADS), and Katz Index of Independence in Activities of Daily Living (ADLs).Results: The mean TFI value in the studied group amounted to 7.13±2.81 (median: 7, interquartile range: 5–9, range [0, 14]). Significant correlations were demonstrated between the values of the TFI and other scales: positive for HADS (r=0.602, P<0.001) and the reverse for MMSE (r=-0.603, P<0.001) and IADL (r=-0.462, P<0.001). Patients with a TFI score ≥5 revealed considerably higher values on HADS (P<0.001) and considerably lower values on the MMSE (P<0.001) and IADL scales (P=0.001).Conclusion: The results for the TFI comply with the results of other scales (MMSE, HADS, ADL, IADL), which confirm the credibility of the Polish adaptation of the tool. Stronger correlations were observed for mental components and the mental scales turned out to be independently related to the TFI in a multidimensional analysis.Keywords: frailty syndrome, acute coronary syndrome, screening tools, elderly